Perfil proteômico de complexos cumulus-oócito e embriões ovinos produzidos in vitro - Passos, José Renato de Sousa (2020)
The first study aimed to describe the proteome of ovine cumulus-oocyte complex (COC) by using a mass spectrometry (MS) with a shotgun proteomics approach. The second study aimed to characterize the proteome of ovine embryos at early development stage. In the first study, the samples were collected from ovaries of adult ewes, and immature CCO proteins as well in vitro mature CCO proteins were subjected to the one-dimensional (1D) sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and identified by MS. In-gel protein digestion and peptide analysis with MS has revealed 2.416 and 2.426\ nonredundant proteins in immature and matured COC, respectively, within three biological replicates with accurate identification. The proteomic data were analyzed according to the gene ontology and a protein-protein interaction network, then several types of proteins involved in immature COC with transcriptional regulation and energy metabolism were identified. Proteins identified in mature COC were mainly related to cell proliferation and enzymes involved in the remodeling of the extracellular matrix, and the proteins differentially expressed were analyzed by False Discovery Rate (FDR <0.05) which were significantly different with abundance in 648 proteins between the immature and mature COC, with 385 up-regulated proteins and 263 down-regulated proteins. This study provides the first accurate characterization in ovine COCs, being possible to identify essentials proteins involved in the oocyte maturation and early embryo development. For the second study, embryo proteins were subjected to one-dimensional (1D) electrophoresis and identified by MS. In-gel protein digestion and peptide analysis with MS revealed 2,292 nonredundant proteins in embryos, within three biological replicates with accurate identification. Proteomic data were analyzed according to the gene ontology, then several types of proteins involved with transcriptional regulation and energy metabolism were identified in embryos. The presence of proteins involved in oocyte protection, among other functions, proteins related to metabolism and energy production, and proteins that are related to cell adhesion and to the organization of the extracellular matrix are emphasized. This study provides the first characterization in ovine embryos, being possible to identify essential proteins involved in embryonic development as possible embryo quality biomarkers.